Spatial–Temporal Analysis of Coupling Coordination Between New Urbanization and Ecological Environment in Ya’an, China - Wei Wei; Lei Xiao; Xiao Zhang; Luyao Jin; Di Wang; Xin Long; Qiaoqiao Yang; Jinxiang Li; Ying Zhou (Land)
Against the backdrop of rapid urbanization, associated environmental problems, including low resource consumption, severe pollution emissions, and low environmental awareness, have become salient. The key to achieving sustainable development in Ya’an lies in accelerating the development of new urbanization while ensuring the preservation of existing ecological advantages. Firstly, this study constructs evaluation index systems for new urbanization and the ecological environment using the Population–Economic–Spatial–Social (PESS) and Pressure–State–Response (PSR) models, respectively. Then, the entropy weight model is used to calculate weights for each secondary indicator of the new urbanization and ecological environment systems. The coupling coordination degree (CCD) and relative development degree (RDD) models are applied to analyze spatial and temporal changes in new urbanization and the ecological environment in Ya’an from 2011 to 2021. Finally, spatial autocorrelation and geographically weighted regression (GWR) models are combined to analyze the factors influencing coupling coordination degree differences among Ya’an’s districts and counties. The results indicate the following: (1) From 2011 to 2021, the CCD of Ya’an shifted from basically balanced to highly balanced, and RDD shifted from new urbanization lag to systematic balanced. (2) The CCD of Ya’an varies significantly among regions, and the spatial differentiation of the effects of different factors has different characteristics.